THE HUMAN CANVAS AND LITERARY ECHO: A STRATEGIC HR FRAMEWORK FOR NURTURING TALENT, ORGANIZATIONAL COMMITMENT, AND NARRATIVE IDENTITY IN THE VISUAL ARTS SECTOR - Kaur, Jaspreet; Middha, Menakshi; Sharma, Gunjan; Desai, Priyanka Parthiv; S S, Jincy; Choudhury, Shyam B.; Kalita, Jyoti Prasad (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The visual arts industry is important in the cultural growth, socialization, and innovation. Nevertheless, the administration of artistic talents in cultural organizations is a specific issue because of the complicated interaction of creativity, identity, and organizational systems. The present study presents a theoretical framework which incorporates strategic human resource management practices, talent nurturing, the role of narrative identity and commitment to organizations within the framework of visual arts organizations. Based on creativity theory, talent management theory, self-determination theory and organizational identity theory, the research hypothesis is that positive HR practices can develop artistic talents and help artists to create meaningful narrative identities. These processes of identity reinforce organization commitment which in the end leads to sustainable creative performance in cultural institutions. The paper also includes the practical implications of the study to museums, galleries, and other arts organizations that are interested in creating enabling environments among the creative professionals. Making use of the insights of both the human resource management and the research of creative industries, the paper contributes to the literature on reminding the significance of identity-based HR practices in supporting artistic communities and maintaining cultural organizations.